2017
DOI: 10.3390/rs9090959
|View full text |Cite
|
Sign up to set email alerts
|

Estimating High Resolution Daily Air Temperature Based on Remote Sensing Products and Climate Reanalysis Datasets over Glacierized Basins: A Case Study in the Langtang Valley, Nepal

Abstract: Near surface air temperature (Ta) is one of the key input parameters in land surface models and hydrological models as it affects most biogeophysical and biogeochemical processes of the earth surface system. For distributed hydrological modeling over glacierized basins, obtaining high resolution Ta forcing is one of the major challenges. In this study, we proposed a new high resolution daily Ta estimation scheme under both clear and cloudy sky conditions through integrating the moderate-resolution imaging spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Lastly, it can be concluded that using TEM and DFM based on the MODIS nighttime LST and with averaged RMSDs of 0.19 and 0.21 °C/100 m, respectively, are expected to generally produce errors for T air interpolation at 1.9 and 2.1 °C in the TP, respectively. Since the errors are generally ~2 °C for daily T air estimation in high mountain areas based on remote sensing products and climate reanalysis data sets (H. Zhang, Zhang, Ye, et al, ; Zhou et al, ), the T air interpolation accuracies from using the MODIS‐estimated TLR are considered to be acceptable for daily T air estimation in the TP. However, the accuracies of the MODIS‐estimated TLR may not be accepted for climatic analysis considering that the climatic warming rates are generally less than 0.1 °C/year for the TP (X. Liu & Chen, ).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, it can be concluded that using TEM and DFM based on the MODIS nighttime LST and with averaged RMSDs of 0.19 and 0.21 °C/100 m, respectively, are expected to generally produce errors for T air interpolation at 1.9 and 2.1 °C in the TP, respectively. Since the errors are generally ~2 °C for daily T air estimation in high mountain areas based on remote sensing products and climate reanalysis data sets (H. Zhang, Zhang, Ye, et al, ; Zhou et al, ), the T air interpolation accuracies from using the MODIS‐estimated TLR are considered to be acceptable for daily T air estimation in the TP. However, the accuracies of the MODIS‐estimated TLR may not be accepted for climatic analysis considering that the climatic warming rates are generally less than 0.1 °C/year for the TP (X. Liu & Chen, ).…”
Section: Resultsmentioning
confidence: 99%
“…MOD11A2 has been validated in dataset comparison studies (Göttsche and Hulley, 2012; Yao et al ., 2018) and investigations reporting high correlation with point data from ground temperature stations (Jain et al ., 2008; Zheng et al ., 2017). These have been used in snow‐melt modelling (Jain et al ., 2010; Shrestha et al ., 2012) and permafrost distribution (Zhou et al ., 2017). More information is available at https://lpdaac.…”
Section: Methods and Datamentioning
confidence: 99%
“…Existing researches reported that about 99% of the LWDR comes from the atmosphere under 700 hPa (Darnell et al, 1983), indicating that the near surface level of the atmosphere is the main contributor of the total LWDR. Fortunately, many researches noted that near-surface air temperature has a good correlation with LST, and the LST was also widely used to estimate or as the surrogate variable of spatially distributed air temperature (Pepin et al, 2016;Zhang et al, 2016;Zhou et al, 2017;Zhu et al, 2017). In addition, according to the Stephen-Boltzmann's law, LST is one of the major components to calculate the LWUP, which shows high correlation with LWDR (Cheng et al, 2017;Zhou & Cess, 2001).…”
Section: Sensor-independent Nonlinear Regression Methodsmentioning
confidence: 99%